Crude protein content in diets associated with intestinal microbiome and metabolome alteration in Huanjiang mini-pigs during different growth stages - Liu, Yating; Azad, Md. Abul Kalam; Zhao, Xichen; Kong, Xiangfeng (Frontiers in Microbiology, 2024)
Introduction Adequate crude protein (CP) content in diets plays a crucial role in the intestinal health of the animal. This study investigated the impacts of CP content in diets on the intestinal microbiome and metabolome profiles in growing Huanjiang mini-pigs. Methods A total of 360 pigs with similar body weight (BW) were allocated for three independent feeding trials based on three different BW stages, including (i) 5–10 kg BW, diets consisting of 14, 16, 18, 20, and 22% CP content; (ii) 10–20 kg BW, diets consisting of 12, 14, 16, 18, and 20% CP content; and (iii) 20–30 kg BW, diets consisting of 10, 12, 14, 16, and 18% CP content. These experiments lasted 28, 28, and 26 days, respectively. Results The results showed that the Shannon and Simpson indices were decreased (p < 0.05) in the ileum of pigs in response to the 14–18% CP compared with the 20% CP content at 5–10 kg BW stage, while diets containing 12 and 14% CP had higher Chao1 (p < 0.05) and Shannon (p = 0.054) indices compared with 18% CP at 20–30 kg BW stage. Compared with the 20% CP, the diet containing 16% CP displayed an increasing trend (p = 0.089) of Firmicutes abundance but had decreased (p = 0.056) Actinobacteria abundance in the jejunum at 5–10 kg BW stage. In addition, a diet containing 16% CP had higher Lactobacillus abundance in the jejunum and ileum compared with the 18, 20, and 22% CP, while had lower Sphingomonas and Pelomonas abundances in the jejunum and Streptococcus abundance in the ileum compared with the diet containing 22% CP (p < 0.05). Diets containing lower CP content altered differential metabolites in the small intestine at the early stage, while higher CP content had less impact. Conclusion These findings suggest that a diet containing lower CP content (16% CP) may be an appropriate dietary CP content for 5–10 kg Huanjiang mini-pigs, as 16% CP content in diet has shown beneficial impacts on the intestinal microbiome and metabolome profiles at the early growth stage of pigs.